1998
DOI: 10.1143/ptps.131.459
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization-Group Resummation of a Divergent Series of the Perturbative Wave Functions of Quantum Systems

Abstract: The perturbative renormalization group(RG) equation is applied to resum divergent series of perturbative wave functions of quantum anharmonic oscillator. It is found that the resummed series gives the cumulant of the naive perturbation series. It is shown that a reorganization of the resummed series reproduce the correct asymptotic form of the wave function at x → ∞ when the perturbation expansion is stopped at the fourth order. A brief comment is given on the relation between the present method and the delta-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…Fundamental analysis of the RG condition, RG 3 , and the RG method is presented in [20][21][22][23]10]. First, it was shown that RG 3 is an envelope equation in the sense of classical differential geometry.…”
Section: Relation Of This Analysis To Other Results About the Rg Methmentioning
confidence: 99%
“…Fundamental analysis of the RG condition, RG 3 , and the RG method is presented in [20][21][22][23]10]. First, it was shown that RG 3 is an envelope equation in the sense of classical differential geometry.…”
Section: Relation Of This Analysis To Other Results About the Rg Methmentioning
confidence: 99%
“…This condition is naturally satisfied if we restrict that t 0 < t < t ′ 0 (or t ′ 0 < t < t 0 ) because the limit t ′ 0 → t 0 is to be taken. Thus when a perturbative expansion is used for constructing X(t; t 0 , W (t 0 )), we demand a more restrictive RG equation as given by [27] …”
Section: Perturbative Rg Equationmentioning
confidence: 99%
“…We remark that a geometrical interpretation of this equation has been given on the basis of the classical theory of envelopes [25,26,27]: When t 0 is varied, X(t; t 0 , W (t 0 )) gives a family of curves with t 0 being a parameter characterizing curves. Then Eq.…”
Section: Perturbative Rg Equationmentioning
confidence: 99%
See 2 more Smart Citations